Sports arbitration: the tribunal arbitral du sport’s experience - Rosero Espinosa, Nicolás (2017)
Often arbitration has been closely related to issues that are likely to be arbitrated, including commercial, corporate or investment matters.However, the sporting matter has been less related to arbitration issues.In the present article, a relatively new and very interesting issue is develop: the sport arbitration, which has been gaining space in various sport organizations to become an instrument of great importance in the sports world. In this way, the author, through the experience of the Tribunal Arbitral Du Sport, shows us the way that sports arbitration has followed, its strengths, its composition and the importance it has achieved in these issues until forging an integral and solid relationship between arbitration and sport.